The Impact of S 51 AC of the Trade Practices Act 1974 upon the Practice of Commercial Leasing in Australia The impact of s 51AC of the Trade Practices Act 1974 upon the practice of commercial leasing - Wong, E.S.K. (Soochow University School of Law, 2009)
The purpose of this paper is to examine the application of the provisions of the Trade Practices Act 1974 (Commonwealth) particularly section 51AC (unconscionable conduct in business transactions) to commercial leases. The Trade Practices Act 1974 (Commonwealth) will also be referred to in this paper as the TPA. In the past few years, there have been increasingly significant concerns from small retailers over unconscionable conduct concerning retail leasing transactions whereby the courts have had to take a more active approach in protecting retail tenancies. For example, in the Australian Competition and Consumer Commission v Leelee Pty Ltd1, illustrates where section 51AC(3)(b) may be used. Another example was A Schroeder Music Publishing Co Ltd v Macauley2, where the section 51AC (3)(b) provision of 'reasonably necessary for the legitimate interests of the corporation has been involved.